LEXICAL INNOVATIONS: KOREANIZED ENGLISH WORDS - Yu S Fayzrakhmanova (Polylinguality and Transcultural Practices, 2016)
This article discusses main types of Koreanized English words. Koreanized English words are lexical innovations created by Koreans for their own communicative purposes using English linguistic material. The author draws the demarcation line between Koreanized English words and a complex phenomenon of “Konglish”.